Valorization of whey proteins and beetroot peels to develop a functional beverage high in proteins and antioxidants - Abdo, Eman M.; Allam, Marwa G.; Gomaa, Mohamed A. E.; Shaltout, Omayma E.; Mansour, Hanem M. M. (Frontiers in Nutrition, 2022)
Introduction Adequate protein and antioxidant intake are crucial for everyone, particularly athletes, to promote muscle performance and prevent muscle damage. Whey proteins are high-quality proteins with high digestibility and bioavailability; beetroot peels are an abundant antioxidant source. Methods The present study was designated to develop a functional beverage based on mixing whey protein isolate (5%) with different concentrations of beetroot peel water extract (1, 2.5, and 5%) and flavored with strawberries puree (5%). In addition, we examined the stability of the physicochemical parameters and the bioactive components of the beverages during cold storage (4°C) for 14 days. Results and discussion Whey protein isolates enriched the juices with stable protein content during the storage (4.65–4.69%). Besides, the extract revealed a concentration-dependent effect on the bioactive components, the antioxidant activity, and the microbial load of the juices; it distinguished the fresh juices by high betalains and nitrate content, 87.31–106.44 mg/L and 94.29–112.59 mg/L, respectively. Beverages with 2.5% peel extract (T2) had the preferable sensory attributes compared to control and other treatments. On day 0, phenolics and flavonoids increased in T2 by 44 and 31% compared to the control, which elevated the scavenging activity of the juice (T2) (P < 0.05). At the end of the storage period (14 days), phenolics and flavonoids of T2 recorded their lowest values, 26.23 and 21.75 mg/mL, respectively. However, they stood higher than phenolics (22.21 mg/mL) (p < 0.05) and flavonoids (18.36 mg/mL) (p > 0.05) of control. Similarly, betalains degraded by 45% to reach 47.46 mg/L in T2, which reduced the redness (a*) and increased the yellowness (b*) values. Conclusion Consequently, whey/strawberry/beetroot peel (5: 5: 2.5 w/v/w) in d.H2O is a functional beverage that provides the body with a high-quality protein and a considerable amount of antioxidants.